Retrospective evaluation of Facial nerve monitoring to prevent nerve damage during robotic drilling in the largest series of patients undergoing the HEARO-procedure - Jaouad Abari; Marco Matulic; Pablo Galeazzi; Masoud Zoka Assadi; Paul Van de Heyning; Vedat Topsakal (PLoS ONE, 2025)
Introduction Robot-assisted cochlear implantation surgery (RACIS) involves the drilling of a keyhole access to the inner ear for cochlear implant placement to treat patients with severe-to-profound sensorineural hearing loss. RACIS with the HEARO-procedure does not require the drilling of a mastoidectomy and posterior tympanotomy to pass through the facial recess. Instead, it directly drills through it guarding a safe distance from both the facial nerve and chorda tympani. Cochlear implantation surgery involves a well described risk for facial nerve injury when passing through the facial recess. Neuromonitoring as a safety protocol gained great importance in conventional CI surgery and is proving its benefits in RACIS. RACIS in the HEARO-procedure involves a customized facial nerve monitoring (FNM) device that was designed and tested in an animal model study. Here, this device was retrospectively assessed in the largest series of patients undergoing the HEARO-procedure. Materials and methods The safety protocol in the HEARO-procedure involves FNM and intra-operative cone-beam CT (CBCT) imaging with a 0.1 mm spatial resolution. The customized FNM device was employed, using both active mono- and bipolar stimulation to estimate the distance to the facial nerve in RACIS. Linear regression was used to determine if the minimum stimulation thresholds (FNM) could significantly predict the intra-operative distance (CBCT) between the drilled trajectory and the facial nerve. Logistic regression was used to calculate if FNM can distinguish distances smaller and greater than 0.4 mm to the facial nerve. Results The minimum stimulation thresholds significantly predicted the distances between the drilling trajectory and the facial nerve for both the monopolar (p = 0.001) and bipolar 3 (p = 0.008) stimulation configuration. Both the monopolar (β = -0.189, S.E. = 0.063, p = 0.003) and bipolar 3 (β = -0.187, S.E. = 0.080, p = 0.019) stimulation configuration are negative and significant predictors of the probability of the distance being smaller than 0.4 mm. Conclusion FNM will alert the surgeon when the drilling trajectory comes closer than 0.4 mm to the facial nerve in RACIS. A linear relationship was observed between the minimum stimulation thresholds and the intra-operative distance towards the facial nerve.